2009
DOI: 10.1007/s10555-008-9168-1
|View full text |Cite
|
Sign up to set email alerts
|

Pak protein kinases and their role in cancer

Abstract: Some of the characteristics of cancer cells are high rates of cell proliferation, cell survival, and the ability to invade surrounding tissue. The cytoskeleton has an essential role in these processes. Dynamic changes in the cytoskeleton are necessary for cell motility and cancer cells are dependent on motility for invasion and metastasis. The signaling pathways behind the reshaping and migrating properties of the cytoskeleton in cancer cells involve a group of Ras-related small GTPases and their effectors, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
226
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(231 citation statements)
references
References 160 publications
1
226
0
1
Order By: Relevance
“…We thought to investigate whether another downstream effector of Rac1, P21-activated kinase (PAK), was involved. In supporting this hypothesis, both Rac1 and PAK1 were found overactivated in colon cancer samples (Esufali and Bapat, 2004;Kumar et al, 2006;Dummler et al, 2009).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…We thought to investigate whether another downstream effector of Rac1, P21-activated kinase (PAK), was involved. In supporting this hypothesis, both Rac1 and PAK1 were found overactivated in colon cancer samples (Esufali and Bapat, 2004;Kumar et al, 2006;Dummler et al, 2009).…”
Section: Introductionmentioning
confidence: 60%
“…Group I PAKs (PAK1, PAK2 and PAK3) were initially identified as effectors of the small GTPases Cdc42 and Rac1 (Manser et al, 1994), but could also be activated by diverse pathways (Bokoch, 2003;Kumar et al, 2006), whereas Group II PAKs (PAK4,PAK5 and PAK6) were identified more recently with their regulation less understood (Wells and Jones, 2010). PAKs have oncogenic functions in a broad range of cancers and their over-activation have been well documented (Kumar et al, 2006;Dummler et al, 2009;Molli et al, 2009). For example, PAK1 phosphorylates Merlin at Ser518 and inhibits its activity in neurofibromatosis (Xiao et al, 2002;Rong et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…PAK1-3 are downstream effector proteins of the small GTPases Rac1/Cdc42. 9,10 Binding of Rac1/ Cdc42 in their active GTP-bound state to the RBD abrogates the interaction of the kinase inhibitory domain (KID) with the kinase domain leading to kinase activation. Kinase activity is induced by either autophosphorylation in trans at pT423/402-PAK1/2 within the activation loop of the kinase domain or may involve a third-party kinase such as phosphoinositide-dependent protein kinase-1 (PDK1).…”
Section: Introductionmentioning
confidence: 99%
“…PAK1 has been reported to be widely overexpressed and/or hyperactivated in various types of benign and malignant cancers (6). PAK1 expression is up-regulated in 40 -50% of primary breast cancers (7,8).…”
mentioning
confidence: 99%